2014
DOI: 10.1111/aphw.12039
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Better Understanding of What Makes Positive Psychology Interventions Work: Predicting Happiness and Depression From the Person × Intervention Fit in a Follow-Up after 3.5 Years

Abstract: Most tested indicators of a person × intervention fit are robust predictors of happiness and depressive symptoms-even after 3.5 years. They might serve for an early estimation of the effectiveness of a positive intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 32 publications
2
73
0
1
Order By: Relevance
“…Their research provides evidence for the effectiveness of PPIs and they identify specific conditions (e.g., individual vs. group vs. online training), which have an impact on the effectiveness of the interventions (see also Bolier et al, 2013). A recent study also supports the notion that the way people work with a PPI can predict a substantial portion of variance in life satisfaction (6%) and depression (10%) about 3.5 years after completion of the intervention (Proyer et al, 2015). Hence, there is broad evidence that encourages further research in this area.…”
Section: Introductionmentioning
confidence: 58%
“…Their research provides evidence for the effectiveness of PPIs and they identify specific conditions (e.g., individual vs. group vs. online training), which have an impact on the effectiveness of the interventions (see also Bolier et al, 2013). A recent study also supports the notion that the way people work with a PPI can predict a substantial portion of variance in life satisfaction (6%) and depression (10%) about 3.5 years after completion of the intervention (Proyer et al, 2015). Hence, there is broad evidence that encourages further research in this area.…”
Section: Introductionmentioning
confidence: 58%
“…The world health organization has considered sleep quality as one of the principles of primary health care on the agenda of the member states and defined it as follows: 'sleep is a physiological mechanism of the body in recovering the lost power and fatigue from physical activity during daily life and is an important criterion to maintain physical and mental health' (19). Since negative emotions are related to affections, general health and poor sleep quality (10), positive psychology aims to carry out studies in relation to anything that gives value to humans' life (20). Results indicated that positive emotional states have a great impact on sleep quality in all stages of life, especially pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…These results show an overall positive link between character strengths and well-being, with some being apparently more influential. Even higher levels of subjective and psychological well-being and health can be achieved by applying character strengths (e.g., Lyubomirsky et al, 2005; Seligman et al, 2005; Gander et al, 2013; Proyer et al, 2014). For example, character strengths use (hope, zest) has been shown to predict subjective well-being and correlated positively with self-esteem in a sample of UK students (Proctor et al, 2011) as well as with positive affect for a sample of UK students (Ouweneel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of well-being were also found in studies focusing on the application of specific character strengths like, e.g., gratitude (Emmons and McCullough, 2003), kindness (Otake et al, 2006) or humor (Gander et al, 2013). The effect of character strengths-based interventions (e.g., using your strengths in a new way every day for 1 week; Seligman et al, 2005) on increasing well-being and decreasing depression over time has also been documented (Gander et al, 2013; Proyer et al, 2014). …”
Section: Introductionmentioning
confidence: 99%